The Influence of Fintech on the National Security System: Law, Economic Potential and Digital Defense Strategy - Djoyonegoro, Ngasiman; Harisudin, Muhammad Noor; Hariyanto, Hariyanto (Faculty of Law, Universitas Pattimura, 2025)
Introduction: Fintech has emerged as a transformative force in the financial sector, bringing significant changes encompassing economic potential and challenges to national security strategies.Purposes of the Research: This research wants to explore the efforts that have been made by countries in dealing with the impact of Fintech on security.Methods of the Research: This research uses a qualitative method with a descriptive analysis approach. This research focuses on qualitative methods and is researched to see the extent of the challenges posed by fintech to the country's resilience systemResults of the Research: The increasing adoption of Fintech also presents challenges to national security digital defense strategies. Threats to data security, cyberattacks, and misuse of financial technology can jeopardize national financial infrastructure, threaten the stability of the financial system, and pose risks to national security. Thus, concerted efforts from governments, financial institutions, and Fintech companies are required to enhance digital defense. Governments need to implement stringent regulations to safeguard Fintech user data and privacy and closely supervise Fintech operations to mitigate the risks of financial technology misuse. Collaboration between governments, financial institutions, and Fintech companies in sharing security intelligence is essential to tackle increasingly complex and organized threats. Additionally, investing in advanced security technology, raising user awareness about security, and strengthening oversight of critical infrastructure are crucial steps in digital defense strategies. Fintech has exerted significant influence on national security, offering vast economic potential while presenting intricate challenges to digital defense strategies. Acknowledging both the potential and challenges, governments and stakeholders must collaborate to create a secure, reliable, and sustainable Fintech ecosystem that fosters economic progress and bolsters overall national security.